PENGARUH DISIPLIN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT. BPR CILEDUG DHANA SEMESTA KOTA TANGERANG - Fathan, Muhamad; Saprudin, Udin (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the positive and significant influence of discipline and motivation variables simultaneously on employee performance at PT. BPR Ciledug Dhana Semesta Tangerang City. The sample used was a saturated sampling technique, totaling 60 employees. Data collection techniques through primary and secondary data. Data analysis techniques use descriptive statistics, validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, t test and f test. The research results show that: (1) Partially there is a positive and significant influence between compensation on employee performance at PT. BPR Ciledug Dhana Semesta Tangerang City, this can be proven from the value ????ℎ???????????????????? 3.534 > ???????????????????????? 1.671 with a significance of 0.003 < 0.05. (2) Partially there is a positive and significant influence between motivation on employee performance at PT. BPR Ciledug Dhana Semesta Tangerang City, this can be proven from the simple linear regression equation y = 3,231+0.874x₂ and the value of ????ℎ???????????????????? 3,034> ???? once 1,671 with a significant 0.001 <0.05. (3) Simultaneously there is a positive and significant influence between discipline and motivation on employee performance at PT. BPR Ciledug Dhana Semesta Kota Tangerang, this can be proven from the multiple linear regression equation Y = -1.100 + 0.296 X₁ + 0.771 ???????????????? 2,380 with level significant 0.000 < 0.05